Back Cover: Catalyst‐Dependent Chemoselective Formal Insertion of Diazo Compounds into C−C or C−H Bonds of 1, 3‐Dicarbonyl Compounds (Angew. Chem. Int. Ed. 32/2018). Issue 32 (11th June 2018) - Liu, Zhaohong; Sivaguru, Paramasivam; Zanoni, Giuseppe; Anderson, Edward A.; Bi, Xihe
Abstract : The construction of all‐carbon quaternary centers by one‐carbon insertions into C−C bonds is a formidable challenge. In their Communication onpage 8927 ff. (Issue 29), X. Bi and co‐workers report on the catalyst‐dependent chemoselective insertion of diazo compounds into 1, 3‐dicarbonyl species. In the presence of AgOTf, the diazo compounds selectively insert into the C(=O)−C bond, affording 1, 4‐dicarbonyl products with an all‐carbon α‐quaternary center. In the presence of Sc(OTf)3, on the other hand, C−H insertion results in α‐C−H alkylation products.